2018
DOI: 10.1175/jamc-d-17-0172.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Extreme Etesians over the Aegean and Implications for Wind Energy Production in Southeastern Europe

Abstract: Episodes of extremely strong northerly winds (known as etesians) during boreal summer can cause hazardous conditions over the Aegean Archipelago (Greece) and represent a threat for the safe design, construction, and operation of wind energy turbines. Here, these extremes are characterized by employing a peak-over-threshold approach in the extended summer season (May–September) from 1989 to 2008. Twelve meteorological stations in the Aegean are used, and results are compared with 6-hourly wind speed data from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Previous studies have shown a robust signal for increase wind power generation potential over the EMED in summer, and in particular over the Aegean Sea associated with the Etesian winds (Bloom et al, ; Hueging et al, ; Koletsis et al, ; Moemken et al, ; Tobin et al, , ). Indeed, the Aegean Sea enjoys a remarkable wind resource, while the average wind speeds (at wind turbines hub height of 80 m) often exceed the 11 m/s, during the intense Etesians (Dafka et al, ). Future anthropogenic emissions will change the strength of near‐surface winds, at desirable wind turbine sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown a robust signal for increase wind power generation potential over the EMED in summer, and in particular over the Aegean Sea associated with the Etesian winds (Bloom et al, ; Hueging et al, ; Koletsis et al, ; Moemken et al, ; Tobin et al, , ). Indeed, the Aegean Sea enjoys a remarkable wind resource, while the average wind speeds (at wind turbines hub height of 80 m) often exceed the 11 m/s, during the intense Etesians (Dafka et al, ). Future anthropogenic emissions will change the strength of near‐surface winds, at desirable wind turbine sites.…”
Section: Discussionmentioning
confidence: 99%
“…The literature describes a wide range of approaches to objectively classify the Etesians . Here in order to be consistent with our previous studies (Dafka et al, 2016(Dafka et al, , 2017(Dafka et al, , 2018, we define intense Etesians as days exceeding the third-quartile (Q3) threshold of 12 UTC observed/simulated SLP differences (ΔP) between Elliniko (PE) and Rhodes (PR; ΔP = PE − PR ≥ Q3). Likewise, days such that median ≤ ΔP < Q3 are defined as moderate Etesians.…”
Section: Classification Of Etesiansmentioning
confidence: 97%
See 1 more Smart Citation
“…Prediction of the frequency, intensity and persistence of Etesians in the summer months is important for ecosystem services, wildfire prevention, air quality forecasts, tourism, energy production and economic development (Athana-sopoulou et al, 2015;Dafka et al, 2018). The synoptic system associated with the Etesians exhibits high predictability compared to the other weather patterns in the EMed (Hochman et al, 2019).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Etesians also contribute to the reduction of pollution events, enhancing pollutant dispersion and improve air quality (Metaxas and Bartzokas, 1994;Melas et al, 1998;Ziomas, 1998;Giakoumi et al, 2009;Poupkou et al, 2011;Tyrlis et al, 2015) whereas strong Etesians can enhance the fast spread of fires in the Aegean islands (Kotroni et al, 2001;Amraoui et al, 2015) and can cause difficulties with sea transport and sailing (Metaxas and Bartzokas, 1994;Koletsis, 2009;Koletsis, Kotroni and Lagouvardos, 2014). Finally, they are viewed as a very effective way to produce low-cost renewable energy due to the stability and persistence of the summer circulation over the Aegean (Zerefos, 1978;Borhan, 1998;Kabouris and Hatziargyriou, 2006;Dafka et al, 2017). These characteristics render the Etesian wind system an important climatic element with significant socioeconomic contribution on human activities for the EMED.…”
Section: The Etesian Wind Systemmentioning
confidence: 99%